Clinical efficacy of one-hole split endoscopy vs. unilateral biportal endoscopy for the treatment of single-segment lumbar spinal stenosis: a retrospective study with 2-year follow-up - Qing, Peidong; Guo, Wenlong; Xie, Shiming; Zhao, Shengxin; Cui, Liqiang; Li, Mingfan; Gong, Shuangquan; Hu, Youpeng (Frontiers in Surgery, 2025)
BackgroundOne-hole split endoscopy (OSE) is a novel endoscopic technique proposed by Chinese scholars in recent years. Currently, data is lacking regarding the long-term efficacy of OSE for treating lumbar spinal stenosis (LSS). This study aimed to compare the long-term efficacy of OSE and unilateral biportal endoscopy (UBE) in LSS treatment.MethodsThe clinical data of 77 patients diagnosed with LSS at our hospital between January 2020 and March 2022 were retrospectively analyzed. Forty-one patients were treated with OSE, and 36 were treated with UBE. Perioperative indicators such as operation time, blood loss, fluoroscopy times, incision length, hospital stay, follow-up time, complications, and C-reactive protein level preoperatively and 3 days postoperatively were recorded. Visual analog score (VAS) and Oswestry disability index (ODI) were recorded preoperatively and at 1, 3, 6, 12, and 24 months postoperatively to evaluate pain and functional disability. The dural sac cross-sectional area (CSA), lumbar range of motion (ROM), and sagittal translation (ST) of the surgical segment were recorded preoperatively and 3 days postoperatively to evaluate lumbar stability. Clinical efficacy was assessed at the final follow-up using the modified Macnab criteria.ResultsVAS and ODI scores significantly improved at each postoperative follow-up in both groups compared with preoperative values (P < 0.05), with no significant difference between the groups (P > 0.05). However, OSE had a shorter operation time, less blood loss, and shorter incision length than UBE (P < 0.05). Postoperative CSA was significantly increased compared to the preoperative CSA (P < 0.05), with no significant difference between the groups (P > 0.05). Postoperative ROM and ST increased; however, there was no significant difference compared to preoperative values (P > 0.05). The complication rates in the OSE (n = 2, 4.88%) and UBE (n = 2, 8.33%) groups were not significantly different (x2 = 0.023; P = 0.880). Clinical efficacy was assessed at the last follow-up using the modified MacNab criteria. Thirty-eight (92.68%) and 34 (94.44%) patients in the OSE and UBE groups, respectively, demonstrated excellent or good efficacy, with no significant difference in the efficacy rate between the groups (x2 = 0.151, P = 0.985).ConclusionOSE and UBE showed satisfactory long-term efficacy and safety for LSS treatment. However, OSE has a shorter operation time, less blood loss, and shorter incision length, and can be an alternative to UBE.